PERILAKU PEMBELIAN MELALUI INTERNET - Ibnu Widiyanto; Sri Lestari Prasilowati (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2015)
This research was designed to investigate web attributes of online buying behavior. Some variables were developed to establish a model, namely web design attractiveness, vendor reputation, perceived ease of transaction, attitudes towards online buying. The variables effects were then tested on online purchase decision. The population was people who purchased via online on Indonesian webs and for their own uses. The sample sizes were 100 respondents. The study concluded that online purchase decision was mostly influenced by web design attractiveness and vendor reputation. Unfortunately the influence of attitude on online purchase was insignificant, although its sign was positive. However, perceived ease of transaction significantly affected attitudes. It recommended development of better vendor reputation and web design attractiveness to stimulate online purchase decision.